Architectural Competitions as an Instrument for 'Urban Rationalization' in the Context of the Discourse of 'Consistency' in Modernity; the Case of Berlin - Eris, Evin; Ozer, Yasemen Say (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
This article discusses some architectural and urban design competition projects, as well as the ideas that influenced them, which have had a significant place in the development of Berlin since World War II. The article focuses on competition projects, beginning with questions regarding which circumstances and mechanisms are used to realize the principles of modernity, and problematizes the extent to which common wisdom is decisive in cultural and intellectual processes in Berlin, which has been configured based on principles of modernity since the late 19th century and early 20th century. With the assumption that the positivist perspective of enlightenment during early phases of modernity constituted the essence of the discourse of consistency, it is intended to analyze how attempts are made to materialize the notion of rationality - a significant feature of the idea of modernity - in architectural competitions, and how it embodies the identity of Berlin. The transformation of Berlin, which can be associated both with modernity and post-modernity due to its political and economic transformations after the period of modernity is also examined. Berlin was selected as the case study for two primary reasons; first, it was where the Eastern and Western blocs met, representing socialist and capitalist systems. Second, Berlin is in the geographical region where modernity was born, and therefore it has often been referred to in rationality-based practices and discourse regarding a modern city. Within the context of reflections of the idea of modernity on both architecture and cities, and with specific reference to the city of Berlin, assessments of entries in architectural competitions held between 1945-2014 during 3 sub-periods defined by critical political, economic, cultural inflection points are made using cartographical method of urban analysis.
Keywords: Architectural competitions and urban design; Berlin; consistency; modernity; rationality; Architecture